Using Historical Sites in East Kalimantan for Education: Challenges and Opportunities - Muhammad Azmi (Yupa: Historical Studies Journal, 2018)
The historical site can be used as a source of learning history, a model of learning history, media history learning, to enhance literacy history or as historical attractions. The utilization based on their shape can be divided into two, direct utilisation and indirect utilization. Constraints encountered in the utilization of the site can be divided into two, the internal problem and external problems. Internal problems in the form of time limitations, limitations of the learning ability of teachers, and facilities and infrastructure limitations. The problem form of external sites. access limitations, limitations, and limitations of supporting personnel funds.